Determinants of smallholders farmers' participation in collective marketing of maize in the central highlands of Kenya - Mogaka, Hezron; Mugwe, Jayne; Ayieko, David, M; Bett, Eric, k (African Journal of Rural Development, 2019)
Collective marketing has been proposed as a solution to the problem of poor access to markets in developing nations. However, smallholders’ market participation is still limited. This study assessed farmers’ perception of the benefits and challenges in collective marketing, and identified the determinants of smallholder farmers’ participation in collective marketing of maize from 126 households in the central highlands of Kenya. Logistic regression model was used to analyze factors explaining farmers’ participation in collective marketing. The key benefits of collective marketing were better prices and low cost of inputs, while the main challenges were poor infrastructure, disagreement among members and lack of credit. Gender of household head, years of farming experience, training on market information search, keeping records, ability to search market information, marketing group size, extension contact frequency and group meeting frequency were significantly associated with farmers participation in collective marketing. Participation in collective marketing could be improved by targeting women already organized in groups, offering training to households on record keeping, enhanced extension contacts, improving marketing group operations and searching for markets.
Article
Keywords: Gender; Kenya; Logistic regression; market information; market trends; poor infrastructure; record keeping